The Transparent and Accountable Management of Sadaqah Movement Funds as a Strengthening of the Kampung Zakat Program in Ciamis - Haqibul Mujib; Rinrin Rianika (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Transparency and accountability in the management of alms movement funds (GESEK) are key to strengthening the zakat village program, as well as developing Islamic social finance. This study aims to analyze the application of the principles of transparency and accountability in the Sadaqah Movement program in Maparah Village, Ciamis, and its impact on increasing collections, and strengthening community social finance. Using a qualitative approach with observation and interview methods, the results showed that the manager successfully implemented information disclosure, periodic reports, accountability mechanisms, and a sustainable evaluation system. The application of these principles not only increases public participation, but also encourages the improvement of social and economic conditions at the community level. This study explains that transparency is carried out by being open to each other with a variety of approaches and media, accountability is carried out by strengthening the ability of administrative managers and administrative instruments in accordance with regulations.